RESPONSE OF CITRUS ROOTSTOCKS TO DIFFERENT SALINITY LEVELS FOR MORPHOLOGICAL AND ANTIOXIDATIVE ENZYME ACTIVITES - U. Seday; O. Gulsen; A. Uzun; G. Toprak (Journal of Animal and Plant Sciences, 2014)
Citrus is the most produced fruit crop and often constrained by salinity due to their geographic distribution. We investigated morphological and antioxidave enzyme responses of six different citrus rootstocks under various NaCl concentrations, including Cleopatra mandarin (Citrus reshni Tan.), sour orange (C. aurantium L.), rough lemon (C. jambhiri Lush.), Volkamer lemon (C. volkameriana Tan & Pasq.), Carrizo citrange(Poncirus trifoliata L. Raf. X C. sinensis L. Osbeck) and trifoliata orange (P. trifoliata Raf.). Morphological and antioxidative enzyme responses of plants grown in hydroponic media containing 0, 45, 90 and 135 mM of NaCl were assessed at day 10, 20, 30, and 40. The highest shoot growth was observed in Cleopatra mandarin whereas trifoliata orange had the lowest shoot growth. Carrizo citrange showed the lowest visible leaf symptoms among the rootstocks and rough lemon produced the highest level of root biomass. A rootstock x NaCl dose x exposure time interaction was detected for enzymatic responses. In general, ascorbate peroxidase (APX; EC: 1.11.1.11) and guaiacol peroxidase (GP; EC: 1.11.1.7) activity in the rootstocks increased with the elevated salt level. Superoxide dismutase (SOD; EC: 1.15.1.1) activity was lowered in leaves of the rootstocks subjected to higher NaCl concentrations. In conclusion, this study indicated complexity of salt tolerance mechanism probably due to complex genetic make-up of the citrus rootstocks used and importance of APX and GP in salt tolerance of Citrus.
Keywords: antioxidative enzyme; Citrus; oxidative stress; salinity; salt stress